Influence of functional classification on skill tests in elite female wheelchair basketball athletes - Tachibana, K.; Mutsuzaki, H.; Shimizu, Y.; Doi, T.; Hotta, K.; Wadano, Y. (Medicina, 2019)
Background and objectives: Wheelchair basketball players are classified into four functional classes according to the player`s "volume of action", characterized by trunk movement and stability. As this classification is based on a kinematic point of view, test items might be differentially affected by the functional classification level. We aimed to clarify field-based skill test items closely related to the functional classification level. Materials and Methods: Twenty-six female wheelchair basketball athletes (Japan National Team candidates) completed seven field-based skill tests (20 m sprint, agility T-test, figure-eight with a ball test, the Yo-Yo 10 m recovery test, and three types of maximal passes), and anthropometric measurements were applied. Results: Significant differences among the classification levels were found for one-hand maximal passes (baseball and hook passes) and the figure-eight with a ball test. Furthermore, performance in the 20 m sprint and 10 m Yo-Yo recovery tests significantly differed between classes 1 and 4. Conclusions: The test items most influenced by the classification levels were one-hand passes, which require trunk stability and balance not only in the horizontal plane, but also in the sagittal and frontal planes. Coaches should consider which test items are strongly affected by the functional classification level when assessing a player`s performance.